2003
DOI: 10.1292/jvms.65.1057
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Loop Diuretics Furosemide and Torasemide on Diuresis in Dogs and Cats

Abstract: ABSTRACT. Torasemide is a new loop diuretic that combines the effects of furosemide and spironolactone. There are no reports on the effects of torasemide in cats and dogs. This study compared the diuretic effects of furosemide and torasemide in cats and dogs. Cats with pressure overload cardiac hypertrophy were given oral placebo, torasemide 0.3 mg/kg, or furosemide 1 mg/kg or 3 mg/kg. Con trol and mitral regurgitation dogs were given oral placebo, torasemide 0.2 mg/kg, and furosemide 2 mg/kg for 7 days. Urine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
81
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(99 citation statements)
references
References 16 publications
8
81
0
5
Order By: Relevance
“…In humans, in terms of mineralocorticoid effects, 25 mg spironolactone is approximately equivalent to 50 mg eplerenone (Kalidindi et al, 2007) is a loop diuretic (Hori et al, 2007), registered in human medicine, which also appears to have a potassium sparing diuretic action, presumably through the antagonism of aldosterone. In the dog, however, although the diuretic actions of torasemide have been demonstrated (Uechi et al, 2003), the precise mode of its potassium sparing diuretic effect has not been clearly characterized in the published literature. This agent will not be considered further in the present review.…”
Section: Aldosterone Receptor Antagonistsmentioning
confidence: 99%
“…In humans, in terms of mineralocorticoid effects, 25 mg spironolactone is approximately equivalent to 50 mg eplerenone (Kalidindi et al, 2007) is a loop diuretic (Hori et al, 2007), registered in human medicine, which also appears to have a potassium sparing diuretic action, presumably through the antagonism of aldosterone. In the dog, however, although the diuretic actions of torasemide have been demonstrated (Uechi et al, 2003), the precise mode of its potassium sparing diuretic effect has not been clearly characterized in the published literature. This agent will not be considered further in the present review.…”
Section: Aldosterone Receptor Antagonistsmentioning
confidence: 99%
“…[15] In animal experiments and one study done with CHF patients, an increase of aldosterone was found after loop diuretic therapy. [10,11,13,14] In in vitro, animal, and human studies in CHF patients, torsemide inhibited aldosterone binding to the receptor, causing an anti-aldosteronic effect with reduced kaliuresis. [10 -14,24] The accurate potassium substitution performed in this study could have influenced aldosterone levels, as aldosterone secretion is dependent on potassium levels.…”
Section: Discussionmentioning
confidence: 99%
“…In this case series, we selected the application of torsemide as a replacement for furosemide to diminish the fluid accumulation caused by CHF, and found that it mitigates clinical sign such as pulmonary edema for a long period of time. Although the expected effects of loop diuretics, including hyponatremia, hypokalemia, hypochloremia, decreased urine specific gravity, and increased BUN and creatinine were observed [13], the quality of life for patients with CHF is also maintained well in these cases. The combination of furosemide and hydrochlorothiazide appears to be effective at combating refractory pulmonary edema, although clinicians must be aware of electrolyte abnormalities including hypokalemia [10].…”
mentioning
confidence: 97%
“…Torsemide, like furosemide inhibits Na − cotransport system [13]. Torsemide has a greater and more regular bioavailability, longer half-life, and longer duration of action than furosemide.…”
mentioning
confidence: 99%
See 1 more Smart Citation